Safe and cost‐effective control of post‐transplantation recurrence of hepatitis B. Issue 1 (18th July 2014) - Takaki, Akinobu; Yagi, Takahito; Yamamoto, Kazuhide
<x xml:space="preserve">Abstract</x> A combination of hepatitis B immunoglobulin (HBIG) and nucleoside/nucleotide analogs (NUC) is the current standard of care for controlling hepatitis B recurrence after orthotopic liver transplantation (OLT). However, long‐term HBIG administration is associated with several unresolved issues, including limited availability and extremely high cost, and thus several protocols for treatment with low‐dose HBIG combined with NUC or HBIG‐free regimens have been developed. This article reviews recent advances in post‐OLT hepatitis B virus (HBV) control and future methodological directions. New NUC such as entecavir, tenofovir or lamivudine plus adefovir dipivoxil combinations induce a very low frequency of viral resistance. The withdrawal of HBIG after several months of OLT under new NUC continuation also has permissible effects. Even after HBV reactivation, NUC can usually achieve viral control when viral markers are strictly followed up. Another approach is to induce self‐producing anti‐HBV antibodies via vaccination with a hepatitis B surface antigen vaccine. However, HBV vaccination is not sufficiently effective in patients to treat liver cirrhosis type B after OLT because immune tolerance to the virus has already continued for several decades. Trials of its safety and cost‐effectiveness are required. This review advocates a safe and economical approach to controlling post‐OLT HBV recurrence.